Architecture and labor - Deamer, Peggy; Rendell, Jane, 1967- (New York, NY : Routledge, 2020)
"Through a collection of 13 essays, Peggy Deamer examines the profession of architecture not as an abstraction, but as an assemblage of architectural workers. What forces prevent architects from empowering ourselves to be more relevant and better rewarded? How can these forces be set aside by new narratives, new organizations and new methods of production? How can we sit at the decision-making table to combat short-term real estate interests for longer term social and ethical value? How can we pull architecture - its conceptualization, its pedagogy, and its enactment - into the 21st century without succumbing to its neoliberal paradigm? In addressing these controversial questions, Architecture and Labor brings contemporary discourses on creative labor to architecture, a discipline devoid of labor consciousness. This book addresses how, not just what, architects produce and focuses not on the past but on the present. It is sympathetic to the particularly intimate way that architects approach their design work while contextualizing that work historically, institutionally, economically, and ideologically. Architecture and Labor is sure to be a compelling read for pre-professional students, academics, and practitioners"--
Craft and Design: "Detail: The Subject of the Object" -- Architectural Work: "Work" -- Technology, BIM and New Work: "BIM and Parametricism" -- Architectural Production and Consumption: "Architectural Work in the Capitalist Context" -- Architectural Work: "Immaterial Labor" -- Antitrust Laws and Architectural Value: "The Sherman Antitrust Laws and the Profession of Architecture" -- Architectural Unionization: "The Missing Unions of Architectural Labor" -- Professionalism and the AIA: "Response to AIA Values" / with Keefer Dunn and Manuel Shvartzberg -- Other Nations' Professional Architectural Associations: "International Architectural Associations: Comparisons and Concerns" -- Architectural Contracts: "Contracts of Relations" -- Architectural Cooperativization: "Socializing Architecture Practice: From Small Firms to Cooperative Models of Organization" / with Aaron Cayer, Shawhin Roudbari, and Manuel Shvartzberg -- Beyond Architecture: "For an Architecture of Radical Democracy" / with Manuel Shvartzberg.
OCLC-licensed vendor bibliographic record.
Keywords: Architectural practice; Labor; ARCHITECTURE / Criticism; ARCHITECTURE / Professional Practice